Reduction of Total Harmonic Distortion in Distribution System with PV Penetration Utilizing D-STATCOM - Yusoff N.B.; Hashim T.J.T.; Xuan L.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric current regulators; Fast Fourier transforms; Harmonic analysis; Harmonic distortion; IEEE Standards; MATLAB; Wave filters; % reductions; Distribution static compensator; Distribution systems; Frame theory; Photovoltaics; Source currents; Synchronoi reference frame theory controller; Synchronous reference frame; Total harmonic distortions; Static synchronous compensators